Platoon movement and maneuvers using PID controller - Raghuraman Varunkumar (2018)
With the emerging trends in autonomous vehicles, the need for effective platoon management system has been gradually gaining its importance. So far most of the platoons in freight transportation have been incorporated with Adaptive Cruise Controlled (ACC) algorithm that could not cater the needs of sophisticated platoons. This has created a need to introduce and implement a wide range of other control algorithms. This dissertation work focuses on incorporating the PID controller algorithm to achieve longitudinal control of a platoon containing ‘n’-vehicles for freight transportation. The novel control algorithm implemented in this work ensures that every vehicle in a platoon is governed for smooth traversal and automated split and merge actions. This control algorithm has been developed in MATLAB and validated by simulating them in VISSIM. The split, merge and lane change actions are simulated for a real-time scenario using platoons. In addition, the developed control algorithm has been ensured to be string stable. The basic ideology behind this is that, the header vehicle is responsible for the platoon and communicates with all the follower vehicles to receive requests and send acknowledgements for smooth completion of the actions mentioned. This will result in an automated platooning in which the header vehicle holds the complete responsibility for making decisions. Hence, this work forms the basis for building a sophisticated platooning system where the drivers will be more into monitoring rather than controlling.